ChemInform Abstract: In situ Generation of Dihydropyridine for the Enantioselective Transfer Hydrogenation of 1, 4‐Benzoxazines. Issue 42 (September 2016) - Aillerie, Alexandre; Gosset, Cyrille; Dumont, Clement; Skrzypczak, Valentin; Champetter, Philippe; Pellegrini, Sylvain; Bousquet, Till; Pelinski, Lydie
Abstract: leading to enantioenriched dihydrobenzoxazines